2003
DOI: 10.14411/eje.2003.085
|View full text |Cite
|
Sign up to set email alerts
|

Mouthparts, gut contents, and retreat-construction by the wood-dwelling larvae of Lype phaeopa (Trichoptera: Psychomyiidae)

Abstract: Abstract. The larvae of Lypephaeopa (Stephens, 1836) are found on dead wood substrates in streams and lakes. Gut content analy ses, scanning electron microscopy of larval mouthparts, and gallery structure revealed characteristics of this habitat preference. The guts of the larvae contained mainly wood fragments whereas other food items (detritus, algae, fungi, inorganic particles) were much rarer. The suitability of the mouthparts to scrape wood surfaces, and the adaptative elongation of the silk-secreting sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…5 Several authors have worked on characterizing the mouthparts of various caddisflies species using scanning electron microscopy (SEM). 5,8,9 (Much remains to be learned about the anatomy and physiology of the caddisfly silk spinning system.) The silks of Trichoptera larvae share several general features with the silks of their terrestrial Lepidopteran relatives, but there are distinct features that may have arisen during its adaptation to aquatic use.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several authors have worked on characterizing the mouthparts of various caddisflies species using scanning electron microscopy (SEM). 5,8,9 (Much remains to be learned about the anatomy and physiology of the caddisfly silk spinning system.) The silks of Trichoptera larvae share several general features with the silks of their terrestrial Lepidopteran relatives, but there are distinct features that may have arisen during its adaptation to aquatic use.…”
Section: Introductionmentioning
confidence: 99%
“…The sensillar inventory of the ovipositor allows spatial orientation in searching for suitable oviposition places and additional proving of the substrate prior to oviposition (Spänhoff et al 2003a). Larvae are specialised in wood exploitation by constructing their retreats mainly from wooden fragments, and exhibit high amounts of wood in their guts (Spänhoff et al 2003b), although their capability of enzymatic wood digestion is rather low (Schulte et al 2003). The balance of ovipositors' benefits and costs has been analysed for crickets by Masaki (1986), giving some evidence for evolutionary co-development of habitat selection for egg deposition by mature females and their ovipositor length.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae of Psychomyiidae construct tunnel-like retreats on surfaces of solid substrates, feeding mainly on the surface biofilm. Tinodes (Curtis, 1834) species could be typically found on surfaces of mineral substrates, such as stones (for example, T. waeneri, T. pallidulus MacLachlan, 1878, T. assimilis MacLachlan, 1865) or calcareous tufa habitats [T. unicolor (Pictet, 1934); Alecke 1998], whereas Lype species [L. phaeopa (Stephens, 1836) and L. reducta (Hagen, 1868)] are specialised on submerged wood (Spänhoff et al 2003b). This is correlated with females choosing different substrates for egg deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known on the capability of aquatic invertebrates to digest refractory components of wood such as cellulose and lignin. A recent study on L. phaeopa showed that the larval guts contained large amounts of wooden fragments (Spa¨nhoff et al, 2003b) but the larvae displayed only a limited enzymatic activity to digest the main wood components such as hemicellulose and cellulose (Schulte et al, 2003). Epixylic biofilms and fungal hyphae penetrating the bark and outermost surface layers of submerged wood (Spa¨nhoff & Gessner, 2004) could be the main nutrient resources for wood inhabiting invertebrates, due to their higher contents of nitrogen compounds compared to the wood itself, but this has not yet been shown.…”
Section: Nutrient Supply Of Larvae and Theoretical Effects Of Shadingmentioning
confidence: 99%
“…The study organism was Lype phaeopa (Psychomyiidae), a caddisfly species whose larvae inhabit submerged wood in streams and lakes (Alderson, 1969). The larval behaviour has been already investigated (Spa¨nhoff et al, 2003b;Spa¨nhoff & Alecke, 2004) indicating a close association of the larvae with submerged wood, which is likely to be predetermined by the females' choice of the oviposition place (Spa¨nhoff et al, 2003a). The larval gut mainly contained wooden fragments, however the enzymatic capacity of larvae to digest the main wood components has been shown to be low (Schulte et al, 2003).…”
Section: Introductionmentioning
confidence: 99%